Manejo de plantas adultas de Panicum maximum cv. Aruana - Correia, Núbia Maria; Perussi, Fábio José [UNESP] (Revista Brasileira de Ciencias Agrarias, 2015)
The present work aimed to study the management of adult plants of Panicum maximum cv. Aruana by glyphosate applied alone and mixed with quizalofop-p-tefuryl associated with the sequential application of glyphosate and mechanical harvest before application. Two experiments were conducted under field conditions. Plants of P. maximum of one experiment were cut and, in the other, no. Six treatments [glyphosate (1.08 and 1.44 kg ha-1), glyphosate (1.08 and 1.44 kg ha-1) in combination with quizalofop-p-tefuryl (0.12 kg ha-1), quizalofop-p-tefuryl (0.12 kg ha-1), and a control without herbicide] were studied, combined with (or without) the sequential application of glyphosate (1.08 kg ha-1), sprayed nine days after the first. In both conditions, cut and not cut, none of the experimental treatments resulted in 100% mortality of plants of P. maximum cv. Aruana. Furthermore, the application of quizalofop-p-tefuryl isolate was ineffective in control the adult plants and its association with glyphosate no added advantages. In both experiments, the application in a single season at 1.44 kg ha-1 glyphosate was sufficient to control plants (>85%). The same occurred with the combination of 1.08 kg ha-1 of glyphosate over sequential 1.08 kg ha-1.
Management of adults plants of Panicum maximum cv. Aruana
Keywords: Colonião grass; Cover crop; Glyphosate; No tillage